Universal Fano factor and anomalous I-V characteristics in weakly interacting quantum dots - Souza, André Maurício Conceição de (2013)
We study interaction effects in quantum dots coupled to perfectly conducting leads via barriers of arbitrary transparencies and embedded in an electromagnetic environment characterized by a fixed external impedance. Combining a recently proposed renormalization group equation for the semiclassical regime of this system with an extended version of circuit theory, we study the Fano factor and the I-V characteristics in the low-temperature and low-energy regime. The Fano factor exhibits a sequence of universal plateaus as a function of the transparencies of the barriers. We also show that a recently discovered quantum transition, at intermediate values of the barrier’s transparencies, leads to an anomalous transport regime characterized by a Fano factor that is the harmonic average of its values in adjacent plateaus. Our result extends a previous classification scheme for mesoscopic conductors.